IT tools and business systems (Tata McGraw-Hill, 2011)
The book is composed exactly as per the syllabus (M1-R4/A1-R4, module 1) prescribed for 'O' and 'A' level syllabus of DOEACC. The objective of the book is to help readers understand the technology that lies beneath the IT revolution.